Thermodynamic survey of a reactive MHD couple stress fluid through saturated porous substances with convective boundary conditions - Alsaud, Huda; Hassan, Anthony R.; İnç, Mustafa; Disu, Akeem B.; Oke, A. S.; Rezapour, Shahram (World Scientific Publ Co Pte Ltd, 2024)
This study explores the thermodynamic behavior of a reactive hydromagnetic liquid flowing through permeable materials, with convective cooling applied to the walls. This study holds practical significance in optimization of thermal management systems and it is crucial for enhancing the efficiency of controlling thermal runaway. The flow is modeled as a system of partial differential equations which are numerically solved. The modified Adomian Decomposition Method and Pade approximation technique are utilized in solving the equations. The results acquired for velocity and temperature distributions are thereby employed to estimate entropy generation rate with critical values over numerous effects of various boundaries over improvement of thermal runaway utilizing Pade approximation technique to show the significant impact of convective cooling term (Biot number) and other thermophysical parameters on the fluid flow. The outcomes show that fluid velocity continuously increases with rising values of inverse couple stress and fluid temperature increases Biot number.
Keywords: Couple stress; porous medium; hydromagnetic; convective cooling; thermal stability; modified Adomian decomposition method (MADM)